Identification and Validation of Epithelial Cell Centre Regulatory Transcription Factors in the Gastric Cancer Microenvironment - Su G; Wang J; Liu S; Fu X; Li Y; Pan G (International Journal of General Medicine)
Guomiao Su,1,* Juan Wang,2,* Shiyue Liu,1,* Xiaonan Fu,1 Yanxi Li,1 Guoqing Pan1 1Department of Pathology, The First Affiliated Hospital of Kunming Medical University, Kunming, Yun Nan, People’s Republic of China; 2Clinical Laboratory, Yunnan Province Third People’s Hospital, Kunming, Yun Nan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanxi Li; Guoqing Pan, Department of Pathology, The First Affiliated Hospital of Kunming Medical University, Kunming, Yun Nan, People’s Republic of China, Email liyanxicuhk@163.com; guoqing_pan@163.comPurpose: To identify the epithelial cell centre regulatory transcription factors in the gastric cancer (GC) microenvironment and provide a new strategy for the diagnosis and treatment of GC.Methods: The GC single-cell dataset was downloaded from the Gene Expression Omnibus (GEO) database. The regulatory mechanisms of transcription factors in both pan-cancer and GC microenvironments were analysed using the Cancer Genome Atlas (TGCA) database. Real-time quantitative PCR (RT-qPCR) was used to determine the mRNA expression levels of Prospero homeobox gene 1 (PROX1) and Endothelial PAS domain-containing protein 1 (EPAS1) in the human gastric mucosal normal epithelial cell line (GES-1) and the GC cell line (AGS). Immunohistochemistry (IHC) was used to determine the amounts of PROX1 and EPAS1 protein expression in GC and adjacent tissues. GC patients’ overall survival (OS) was tracked through outpatient, Inpatient case inquiry, or phone follow-up.Results: The single-cell data from GSE184198 was re-annotated, resulting in nine cell subsets: T cells (13364), NK cells (606), B cells (2525), Epithelial cells (2497), DC cells (1167), Fibroblast cells (372), Endothelial cells (271), Neutrophils cells (246) and Macrophage cells (420). Analysis of cell subgroup signalling pathways revealed that communication intensity between epithelial cells and smooth muscle cells was highest. Transcription factors PROX1 and EPAS1 were notably active in epithelial cells. Cell communication analysis indicated that IFNG may interact with IFNGR1/2 and LIF with IL6ST and LIFR to regulate the downstream PROX1 and EPAS1. PROX1 and EPAS1 were upregulated and negatively correlated with tumour mutation burden (TMB). They also exhibited high positive correlations with immune checkpoints CTLA4 and PDCD1LG2, as well as with chemokines CCL24 and CXCL12 and their receptors CCR3 and CCR4. Additionally, PROX1 and EPAS1 were positively correlated with immunosuppressive factors ADORA2A, CD160, IL10, TGFBR1, KDR and CSF1R, as well as with immunostimulators CD276, PVR, TNFRSF25, ULBP1, CXCL12 and ENTPD1. In GC tissues and AGS, PROX1 and EPAS1 were both substantially expressed. In the meantime, they showed a positive correlation with clinicopathological features such TNM stage and degree of differentiation. In GC patients, the up-regulated group’s PROX1 and EPAS1 prognosis was noticeably poorer than the down-regulated group’s.Conclusion: PROX1 and EPAS1 are likely central regulatory transcription factors in the epithelial cells of the GC environment, regulated by IFNG and LIF. They may contribute to GC progression by modulating the tumour’s immune microenvironment.Keywords: PROX1, EPAS1, GC, tumour microenvironment, transcription factor, cell communication